Look Before You “Lock”: Standards, Tipping, and the Future of Patent Misuse After Princo - Suarez, Christopher (Science and Technology Law Review, 2012)
In network industries, consumers do not always prefer single standards. Setting aside antitrust principles, the Federal Circuit implicitly assumed in Princo that consumers preferred a single standard in the CD-R/RW industry when it held that a patent suppression agreement did not constitute patent misuse. But some network industries can—and do—converge toward multiple standards, and antitrust analyses can be informative in this context. As this Article shows, patent suppression agreements may still “leverage” existing patents in ways that unlawfully expand their scope. This Article argues that courts must consider consumers’ demand-side preferences when they analyze patent misuse claims in network industries, and it proposes a quid-pro-quo rule that incentivizes demand-side analyses by the private sector. This rule would render suppression agreements per se legal in exchange for a commitment to release suppressed technologies into the public domain after a short time-frame, but would also support thorough patent misuse scrutiny in cases where firms refuse to make such a commitment. This rule could move us toward better empirical understandings of consumers’ preferences in network industries, preserve judicial economy in the patent misuse area, and better ensure that superior standards prevail in the marketplace.